Lithium-containing material and preparation method thereof, pre-lithiated negative pole piece and lithium-containing battery
A lithium-containing material with a core-shell structure addresses the stability and safety issues in silicon-based electrodes by stabilizing pre-lithiation, enhancing lithium ion extraction and improving battery performance.
Patent Information
- Application Number
- CN202310721150.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
Existing lithium-ion battery negative electrode materials, particularly silicon-based materials, suffer from volume expansion leading to structural degradation, loss of electrical contact, and decreased cycle performance due to the consumption of lithium ions, necessitating improved pre-lithiation methods to enhance stability and safety.
A lithium-containing material with a core-shell structure, comprising a lithium active core, a silicon-lithium alloy or lithium silicate buffer layer, and a lithium fluoride/lithium carbonate passivation layer, is developed to stabilize the pre-lithiation process, preventing dendrite formation and improving lithium ion extraction kinetics.
The core-shell structure enhances the stability and safety of pre-lithiation, allowing for a uniformly distributed pre-lithiation layer that improves the initial coulombic efficiency and cycle life of lithium batteries.
Smart Images

Figure CN119153638A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium-ion batteries, and in particular to a lithium-containing material and a preparation method thereof, a pre-lithiated negative electrode plate and a lithium-containing battery. Background Art
[0002] In recent years, with the rapid development of new energy vehicles, smart grids, and distributed energy storage, the development of lithium-ion batteries with high energy density, high safety, and long cycle life has become a research hotspot in the field of energy storage. The improvement of battery energy density mainly depends on the development of key electrode materials, such as the continuous improvement of the capacity of positive and negative electrode materials. The capacity of existing lithium-ion battery negative electrode materials has reached its limit. In order to meet the energy needs of the new generation and improve the energy density of batteries, it is of great significance to develop new lithium battery negative electrode materials.
[0003] Among the new negative electrode materials, silicon materials have attracted much attention due to their high theoretical capacity, abundant reserves, and low discharge voltage. However, silicon materials have a huge volume expansion (>300%) during the process of lithium insertion and extraction, which causes the negative electrode materials to pulverize and fall off, forming "dead silicon", and eventually causing the negative electrode materials to lose electrical contact and cause the battery to fail. Secondly, repeated volume expansion and contraction will also cause the SEI film on the surface to be continuously destroyed and generated, continuously consuming the positive electrode's Li + , resulting in a decrease in the battery coulombic efficiency. These problems ultimately lead to a sharp deterioration in the battery cycle performance, seriously affecting the battery life.
[0004] Pre-lithiation is to use additional lithium to make up for the lithium consumed in silicon-oxygen battery systems, which can improve the initial efficiency of the battery, reduce the loss of positive lithium ions, and increase the cycle life of silicon and other battery systems. The role of pre-lithiation reagents in the pre-lithiation process is not insignificant. At present, the commonly used negative electrode pre-lithiation reagents are mainly lithium powder and lithium belt. Among them, lithium belt processing is difficult, and the degree of pre-lithiation is difficult to control. Researchers at FMC in the United States proposed that adding lithium powder to lithium-ion batteries can effectively offset the above-mentioned irreversible capacity. Lithium powder dissolves and releases lithium ions during the operation of the battery to make up for the lithium ions consumed during the formation of the SEI film. The addition of lithium powder effectively offsets the loss of lithium ions, improves the initial charge and discharge efficiency of the battery, and then increases the specific energy of the battery (the battery capacity is increased by 10-20%). However, due to its high reactivity and high specific surface area, pure lithium powder is easy to react with oxygen, nitrogen, moisture, etc. in the air during use to explode, and there is an extremely high safety risk. Therefore, further improvements are needed in the stability and safety of pre-lithiation materials. Summary of the invention
[0005] The purpose of the present disclosure is to provide a lithium-containing material and a preparation method thereof, a pre-lithiation negative electrode plate and a lithium-containing battery, which can effectively improve the initial coulombic efficiency of the battery and significantly improve the stability and safety of the pre-lithiation material.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present disclosure provides a lithium-containing material, which includes lithium-containing particles with a core-shell structure; the lithium-containing particles include a core, a buffer layer coated on the outer surface of the core, and a passivation layer coated on the outer surface of the buffer layer; the passivation layer is formed as an outer shell of the core-shell structure; wherein the core contains a lithium active component and a matrix material, and the matrix material is selected from one or two of silicon and silicon monoxide; the buffer layer contains a silicon-lithium alloy or a lithium silicate; and the passivation layer contains lithium fluoride and lithium carbonate.
[0007] Optionally, based on the total weight of the lithium-containing particles, the content of the core is 5 to 95% by weight, preferably 80 to 95% by weight; the content of the buffer layer is 5 to 35% by weight, preferably 5 to 10% by weight; the content of the passivation layer is 1 to 10% by weight, preferably 1 to 6% by weight;
[0008] Optionally, the average particle size of the lithium-containing particles is 0.01 to 5 μm; and the thickness of the passivation layer of the lithium-containing particles is 1 to 500 nm.
[0009] A second aspect of the present disclosure provides a method for preparing a lithium-containing material, comprising the following steps:
[0010] S1, mixing metallic lithium with a matrix material, and subjecting the mixture to ball milling to obtain a raw material mixture, wherein the matrix material is selected from one or both of silicon and silicon monoxide;
[0011] S2, mixing the raw material mixture with a composite solution and performing a stabilization treatment; wherein the composite solution comprises a carbonate compound and a fluorine-containing compound;
[0012] Steps S1 to S2 are respectively carried out under inert conditions.
[0013] Optionally, in step S1, the weight ratio of the metal lithium to the matrix material is (2-50):1, preferably (5-20):1; optionally, the metal lithium is selected from one or more of lithium ingots, lithium wires, lithium powders or lithium sheets; preferably, in the matrix, silicon is a powder, the average particle size of the silicon powder is 0.5-10 μm, and the BET specific surface area is 0.1-50 m 2 / g; the silicon oxide is a powder, the average particle size of the silicon oxide powder is 1 to 20 μm; the BET specific surface area is 0.5 to 100 m 2 / g.
[0014] Optionally, in step S1, the conditions for the ball milling treatment include: a rotation speed of 300 to 2000 r / min, preferably 500 to 1000 r / min; a time of 6 to 72 h, preferably 10 to 48 h; and a ball-to-material ratio of (1 to 50):1, preferably (10 to 20):1.
[0015] Optionally, in step S2, the carbonate compound is selected from one or more of ethylene carbonate, propylene carbonate, diethyl carbonate and dimethyl carbonate;
[0016] The fluorine-containing compound is selected from one or more of lithium hexafluorophosphate, phosphorus pentafluoride and hydrofluoric acid;
[0017] Preferably, the weight ratio of the carbonate compound to the fluorine-containing compound in the composite solution is (1-50):1; preferably (5-20):1;
[0018] Optionally, in step S2, the weight ratio of the raw material mixture to the composite solution is 1:(0.01-1), preferably 1:(0.5-1).
[0019] Optionally, in step S2, the conditions for the stabilization treatment include: a ball milling speed of 200 to 1000 r / min, preferably 200 to 500 r / min; a time of 6 to 72 h, preferably 10 to 20 h; and a ball-to-material ratio of (1 to 50):1, preferably (10 to 20):1.
[0020] Optionally, after step S2, the method further comprises:
[0021] Drying the product obtained by the stabilization treatment to obtain a lithium-containing material;
[0022] Preferably, the drying treatment temperature is 60-100° C.; the drying time is 2-12 hours; preferably, the drying is performed in a vacuum drying oven.
[0023] A third aspect of the present disclosure provides a lithium-containing material prepared according to the method described in the second aspect of the present disclosure.
[0024] A fourth aspect of the present disclosure provides a pre-lithiation negative electrode plate, wherein the pre-lithiation negative electrode plate comprises the lithium-containing material described in the first and third aspects of the present disclosure.
[0025] Optionally, the pre-lithiation negative electrode plate comprises a negative electrode active material and the lithium-containing material;
[0026] Optionally, the negative electrode active material is selected from one or more of silicon oxide negative electrode materials, graphite negative electrode materials, silicon-carbon negative electrode materials and silicon negative electrode materials;
[0027] Preferably, the weight ratio of the negative electrode active material to the lithium-containing material is 1:(0.01-0.5), preferably 1:(0.01-0.1);
[0028] Optionally, the lithium-containing material is coated on the surface of the negative electrode active material coating in the form of a coating; preferably, the coating thickness of the lithium-containing material is 1 to 500 μm, preferably 50 to 200 μm.
[0029] A fifth aspect of the present disclosure provides a lithium-containing battery, comprising the pre-lithiation negative electrode plate described in the fourth aspect of the present disclosure.
[0030] Through the above technical scheme, the present disclosure provides a stable lithium-containing material and a preparation method thereof, a pre-lithiation negative electrode plate and a lithium-containing battery. The stable metal lithium powder provided by the present disclosure has a core-shell structure, including a core, a buffer layer and an outer shell; the core is a lithium active core, the buffer layer is a lithium silicon alloy / lithium silicate layer, and the outer shell is a lithium fluoride / lithium carbonate passivation layer, wherein the buffer layer is a lithium silicon alloy / lithium silicate layer as a rigid layer, which can avoid the formation of lithium dendrites during the pre-lithiation of the metal lithium powder; the lithium fluoride / lithium carbonate passivation layer is a component of the battery SEI film, has good compatibility with the battery system, and will not affect the electrochemical performance of the battery system, and the passivation layer avoids direct contact between the internal active lithium and the outside world, which can improve the stability of the material. In addition, the stable metal lithium powder provided by the present disclosure has a small particle size. When the battery pole plate is pre-lithiation treated, a uniformly distributed and dense pre-lithiation layer can be formed on the surface of the silicon oxygen negative electrode and other pole plates, which can improve the kinetics of lithium metal deintercalation and ion extraction during pre-lithiation, and the pre-lithiation effect is better. The stable metallic lithium powder provided by the present invention has high stability and storage life, is convenient for safe transportation, storage and use, and can be widely used as a pre-lithium supplement additive for lithium battery electrode materials to solve the problem of low initial efficiency of lithium batteries, thereby improving the comprehensive performance of lithium batteries such as capacity and cycle life.
[0031] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0033] Figure 1 An exemplary structural diagram of the Han Li material provided by the present disclosure;
[0034] Figure 2 This is a scanning electron microscope photograph of the lithium-containing material prepared in Example 1;
[0035] Figure 3This is a high-magnification scanning electron microscope photo of the lithium-containing material prepared in Example 1;
[0036] Figure 4 This is a transmission electron microscope photo of the lithium-containing material prepared in Example 1;
[0037] Figure 5 The X-ray diffraction pattern of the lithium-containing material prepared in Example 1;
[0038] Figure 6 The Li 1s X-ray photoelectron high-resolution scanning spectrum of the lithium-containing material prepared in Example 2;
[0039] Figure 7 The C1s X-ray photoelectron high-resolution scanning spectrum of the lithium-containing material prepared in Example 3;
[0040] Figure 8 The O1s X-ray photoelectron high-resolution scanning spectrum of the lithium-containing material prepared in Example 3;
[0041] Fig. 9 The F1s X-ray photoelectron high-resolution scanning spectrum of the lithium-containing material prepared in Example 3;
[0042] Fig.10 This is the first charge and discharge curve of a battery containing lithium material prepared using Example 1 of the present disclosure at a current density of 0.2C. DETAILED DESCRIPTION
[0043] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0044] In a first aspect, the present disclosure provides a lithium-containing material, which comprises lithium-containing particles of a core-shell structure; the lithium-containing particles comprise a core, a buffer layer coated on the outer surface of the core, and a passivation layer coated on the outer surface of the buffer layer; the passivation layer is formed as an outer shell of the core-shell structure; wherein the core comprises a lithium active component and a matrix material, and the matrix material is selected from one or both of silicon and silicon monoxide; the buffer layer comprises a silicon-lithium alloy or a lithium silicate; and the passivation layer comprises lithium fluoride and lithium carbonate.
[0045] The present disclosure provides a lithium-containing material. The stable metal lithium powder provided by the present disclosure has a core-shell structure, including a core, a buffer layer and an outer shell; the core is a lithium active core, the buffer layer is a lithium silicon alloy or a lithium silicate layer, and the outer shell is a passivation layer containing lithium fluoride and lithium carbonate, wherein the buffer layer is a lithium silicon alloy / lithium silicate layer as a rigid layer, which can avoid the formation of lithium dendrites during the pre-lithiation of the metal lithium powder; the lithium fluoride / lithium carbonate passivation layer is a component of the battery SEI film, has good compatibility with the battery system, and will not affect the electrochemical performance of the battery system, and the passivation layer avoids direct contact between the internal active lithium and the outside world, which can improve the stability of the material. In addition, the stable metal lithium powder provided by the present disclosure has a small particle size. When the battery pole piece is pre-lithiated, a uniformly distributed and dense pre-lithiation layer can be formed on the surface of the silicon oxygen negative electrode and other pole pieces, which can improve the kinetics of lithium metal deintercalation and ion extraction during pre-lithiation, and the pre-lithiation effect is better. The stable metallic lithium powder provided by the present invention has high stability and storage life, is convenient for safe transportation, storage and use, and can be widely used as a pre-lithium supplement additive for lithium battery electrode materials to solve the problem of low initial efficiency of lithium batteries, thereby improving the comprehensive performance of lithium batteries such as capacity and cycle life.
[0046] In one embodiment, based on the total weight of the lithium-containing particles, the content of the core is 5 to 95 weight %; the content of the buffer layer is 5 to 35 weight %; and the content of the passivation layer is 1 to 10 weight %.
[0047] In a preferred embodiment, based on the total weight of the lithium-containing particles, the content of the core is 80-95 weight %, the content of the buffer layer is 5-10 weight %, and the content of the passivation layer is 1-6 weight %. The lithium-containing material provided in this embodiment can have higher stability and can obtain higher first coulombic efficiency in battery applications.
[0048] In the present disclosure, the contents of the core, buffer layer and passivation layer of the lithium-containing particles are calculated by ratio.
[0049] In one embodiment, the average particle size of the lithium-containing particles is 0.01 to 5 μm, preferably 0.05 to 1 μm.
[0050] In a preferred embodiment, the thickness of the passivation layer of the lithium-containing particles is 1 to 500 nm, preferably 20 to 200 nm. When the thickness of the passivation layer is within the range of this embodiment, the activity of the internal lithium can be maximized under the premise of ensuring the stability of the lithium-containing particles. The thickness of the passivation layer of the lithium-containing particles in the present disclosure can be measured by electron microscope photos.
[0051] A second aspect of the present disclosure provides a method for preparing a lithium-containing material, comprising the following steps:
[0052] S1, mixing metallic lithium with a matrix material, and subjecting the mixture to ball milling to obtain a raw material mixture, wherein the matrix material is selected from one or both of silicon and silicon monoxide;
[0053] S2, mixing the raw material mixture with a composite solution and performing a stabilization treatment; wherein the composite solution comprises a carbonate compound and a fluorine-containing compound;
[0054] Steps S1 to S2 are respectively carried out under inert conditions.
[0055] The present invention provides a method for preparing a lithium-containing material, wherein firstly, metallic lithium and a matrix material (silicon or silicon oxide) are subjected to ball milling treatment: (1) when a porous silicon matrix is used, a portion of the metallic lithium is confined in the pores of the porous silicon-based material in the form of metallic lithium, and lithium is released during the charge and discharge cycle, thereby replenishing the consumption and loss of lithium ions during the battery cycle and improving the cycle stability; and when the metallic lithium content is relatively high, a portion of the metallic lithium can also react with oxygen on the porous silicon-based material powder to generate lithium oxide, thereby solving the problem of reduced initial coulombic efficiency of silicon itself, and at the same time, acting as a buffer medium to buffer the volume expansion during the cycle, thereby making the material structure more stable; (2) when a silicon oxide matrix is used, a portion of the metallic lithium reacts with oxygen in the silicon oxide to generate The synthesis of lithium silicate and lithium oxide can solve the problem of reduced initial coulombic efficiency of silicon oxide itself. At the same time, it can act as a buffer medium to buffer the volume expansion during the cycle, making the material structure more stable. Another part of the metallic lithium is reserved in the silicon oxide material to supplement lithium during the charge and discharge cycle, supplement the consumption and loss of lithium ions during the battery cycle, and improve the capacity cycle stability. The reaction product on the surface of the porous silicon matrix and the silicon oxide matrix serves as a buffer layer. The raw material mixture is then mixed with the composite solution and stabilized, further realizing the in-situ coating of the passivation layer (shell) on the outside of the core and the buffer layer. The carbonate compounds in the composite solution are converted into lithium carbonate, and the fluorine-containing compounds are converted into lithium fluoride, which can significantly improve the stability of the lithium powder.
[0056] In a specific embodiment, in steps S1 and S2, the inert atmosphere comprises one or more of nitrogen, helium, neon, argon, krypton and xenon; the water content of the inert atmosphere is less than 0.1 wt%, and the oxygen content is less than 0.1 wt%. In the above embodiment, the preferred inert gas environment can further prevent lithium from reacting with oxygen and water in the environment, making the material structure more stable.
[0057] In the present disclosure, the ball milling process and the stabilization process are both performed using a conventional ball mill.
[0058] In one embodiment, in step S1, the weight ratio of the metallic lithium to the matrix material is (2-50):1, preferably (5-20):1.
[0059] In a specific embodiment, the metallic lithium is selected from one or more of lithium ingots, lithium wires, lithium powders or lithium sheets;
[0060] In the matrix, silicon is in powder form, the average particle size of the silicon powder is 0.5 to 10 μm, and the BET specific surface area is 0.1 to 50 m 2 / g; the silicon oxide is a powder, the average particle size of the silicon oxide powder is 1 to 20 μm; the BET specific surface area is 0.5 to 100 m 2 / g.
[0061] In the present disclosure, other inorganic material particles, such as zinc oxide, magnesium oxide and other inorganic material particles, may be added to the matrix material as required.
[0062] The raw materials used in the present invention can be purchased through common channels or prepared by known preparation methods.
[0063] In one embodiment, in step S1, the conditions of the ball milling treatment include: a rotation speed of 300 to 2000 r / min, a time of 6 to 72 hours, and a ball-to-material ratio of (1 to 50):1.
[0064] In a preferred embodiment, in step S1, the conditions of the ball milling treatment include: a rotation speed of 500 to 1000 r / min, a time of 6 to 72 hours, and a ball-to-material ratio of (1 to 20): 1. Ball milling according to this embodiment helps to make the metallic lithium and the matrix material more evenly dispersed, thereby improving the performance of the lithium-containing material.
[0065] In one embodiment, in step S2, the carbonate compound is selected from one or more of ethylene carbonate, propylene carbonate, diethyl carbonate and dimethyl carbonate; preferably one or two of ethylene carbonate and propylene carbonate;
[0066] The fluorine-containing compound is selected from one or more of lithium hexafluorophosphate, phosphorus pentafluoride and hydrofluoric acid; preferably one or two of lithium hexafluorophosphate and phosphorus pentafluoride.
[0067] In a preferred embodiment, the weight ratio of the carbonate compound to the fluorine-containing compound in the composite solution is (1-50):1; preferably (5-20):1.
[0068] In one embodiment, in step S2, the weight ratio of the raw material mixture to the composite solution is 1:(0.01-1), preferably 1:(0.5-1). Stabilization treatment according to the preferred weight ratio of the present disclosure can obtain an in-situ coating passivation layer with better performance.
[0069] In a specific implementation manner, in step S2, the conditions for the stabilization treatment include: a ball milling speed of 200 to 1000 r / min; a time of 6 to 72 hours; and a ball to material ratio of (1 to 50):1.
[0070] In a preferred embodiment, in step S2, the stabilization treatment conditions include: ball milling speed of 200-500 r / min; time of 10-20 h; ball to material ratio of (1-20): 1. The passivation layer coating effect is better according to this embodiment, and the thickness of the passivation layer can be within an appropriate range.
[0071] In a specific implementation manner, after step S2, the method further includes:
[0072] The product obtained by the stabilization treatment is dried to obtain a lithium-containing material.
[0073] In a preferred embodiment, the drying treatment temperature is 60-100° C.; the drying time is 2-12 hours; preferably, the drying is performed in a vacuum drying oven.
[0074] A third aspect of the present disclosure provides a lithium-containing material prepared according to the method described in the second aspect of the present disclosure.
[0075] A fourth aspect of the present disclosure provides a pre-lithiation negative electrode plate, wherein the negative electrode plate comprises the lithium-containing material described in the first and third aspects of the present disclosure.
[0076] The lithium-containing material provided in the present disclosure can be used in combination with existing conventional negative electrode active components.
[0077] In a preferred embodiment, the pre-lithiation negative electrode plate comprises a negative electrode active material and the lithium-containing material;
[0078] Optionally, the negative electrode active material is selected from one or more of silicon monoxide negative electrode material, graphite negative electrode material, silicon-carbon negative electrode material and silicon negative electrode.
[0079] The negative electrode active material used in the present disclosure is a negative electrode material known in the art, which can be purchased through conventional channels or prepared by known methods.
[0080] In a preferred embodiment, the weight ratio of the negative electrode active material to the lithium-containing material is 1:(0.01-0.5), preferably 1:(0.01-0.1).
[0081] According to the present disclosure, the negative electrode plate can be prepared by conventional processes in the art.
[0082] In a specific embodiment, the negative electrode plate is prepared by a preparation method comprising the following steps:
[0083] (1) Weighing the negative electrode active material, the conductive agent, and the binder in a ratio of (7-8.9): (0.1-2): 1, adding solvent water to adjust the slurry viscosity, and stirring for 3-5 hours to obtain a negative electrode mixed slurry; wherein the conductive agent and the binder can be selected from materials conventionally selected in the art;
[0084] (2) coating the negative electrode mixed slurry on a copper foil current collector, and then drying and rolling to obtain a non-pre-lithiation negative electrode sheet;
[0085] (3) dispersing the lithium-containing material in an N-methylpyrrolidone (NMP) solution containing 5 to 20 weight percent polyvinylidene fluoride (PVDF) and stirring the solution to prepare a lithium powder slurry, wherein the solid content of the lithium powder is 5 to 20 weight percent;
[0086] (4) coating the lithium powder slurry on the surface of the non-pre-lithiated negative electrode obtained in step (2) with a coating thickness of 1 to 500 μm, preferably 50 to 200 μm; and obtaining a pre-lithiated negative electrode after vacuum drying and roller pressing.
[0087] The drying and roller pressing treatment can be carried out according to conventional methods in the art.
[0088] A fifth aspect of the present disclosure provides a lithium-containing battery, which comprises the pre-lithiation negative electrode plate described in the fourth aspect of the present disclosure.
[0089] The electrolyte, diaphragm and other materials used in the lithium-containing battery are all reagents conventionally selected in the art.
[0090] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.
[0091] In the following examples, the specific testing methods are as follows:
[0092] The BET specific surface area was tested using the specific surface area and pore size analyzer JW-BK100;
[0093] The SEM test method is scanning electron microscope, and the instrument model is S4800 of Hitachi, Japan;
[0094] The XRD test method is an X-ray diffractometer, and the instrument model is the X'Pert PRO powder X-ray diffractometer from PANalytical;
[0095] The XPS test method is X-ray photoelectron spectrometer, and the instrument model is VG ESCALAB;
[0096] The test method for electrochemical cycle performance is the blue electric test system, and the instrument model is CT3001A.
[0097] In the following examples and comparative examples, commercially available silicon oxide powder was used, with an average particle size of 2 to 10 μm. The chemical formula of the silicon oxide powder is SiO x , where 0.5≤x<2.
[0098] The chemical reagents used in the following examples and comparative examples are all common commercially available products.
[0099] Example 1
[0100] Under argon environment, weigh 2g of lithium metal ingot and 0.2g of silicon oxide and place them in a zirconium oxide ball mill (the weight ratio of lithium metal to matrix material is 10:1), seal and transfer to a planetary ball mill for ball milling, the ball-to-material ratio of the ball milling is 20:1, the diameter of the zirconium balls is 5.5mm, 3.0mm, 2.0mm, the ratio is 2:5:3, the ball milling speed is 500r / min, and the ball milling time is 12h. Then add a total of 2.2g of ethylene carbonate and lithium hexafluorophosphate mixed solution to continue ball milling (the weight ratio of the raw material mixture to the composite solution is 1:1; the weight ratio of carbonate compounds to fluorine-containing compounds in the composite solution is 20:1), the ball milling speed is 350r / min, and the ball milling time is 10h. After centrifugation, dry in a vacuum drying oven at a drying temperature of 80℃ for 5h to obtain stable lithium metal powder, recorded as L-1.
[0101] Figure 2 This is a SEM image of the stable metal lithium powder L-1 prepared in Example 1. As can be seen from the image, the particle size of the stable metal lithium powder is in the range of 0.05 to 2 μm.
[0102] Figure 3 This is a high-magnification SEM image of the stable metal lithium powder prepared in Example 1. It can be clearly seen from the image that the stable metal lithium powder has a dense and complete passivation layer.
[0103] Figure 4 This is a TEM image of the stable metal lithium powder prepared in Example 1. It can be clearly seen from the image that the stable metal lithium powder includes a passivation layer, a buffer layer and a core structure.
[0104] Figure 5 This is the X-ray diffraction spectrum of the stable metal lithium powder prepared in Example 1. It can be seen from the spectrum that obvious diffraction peaks of lithium silicon alloy and lithium silicate appear in the stable metal lithium powder product, indicating that the stable metal lithium powder prepared in this example has lithium silicon alloy and lithium silicate as a buffer layer.
[0105] Comparative Example 1
[0106] This comparative example refers to the preparation method of Example 1, which is different from Example 1 in that silicon dioxide is not added, and the rest of the process is the same as Example 1. The obtained lithium-containing material is recorded as D-1.
[0107] Comparative Example 2
[0108] This comparative example refers to the preparation method of Example 1, and the difference from Example 1 is:
[0109] The composite solution contains only pure ethylene carbonate and does not contain lithium hexafluorophosphate; the rest of the process is the same as in Example 1, and the obtained lithium-containing material is recorded as D-2.
[0110] Comparative Example 3
[0111] This comparative example refers to the preparation method of Example 1, and the difference from Example 1 is:
[0112] The composite solution contains only lithium hexafluorophosphate (using cyclohexane as solvent) and does not contain ethylene carbonate; the rest of the process is the same as in Example 1, and the obtained lithium-containing material is recorded as D-3.
[0113] Example 2
[0114] Under argon environment, weigh 2g of metal lithium ingot and 1g of micron silicon and place them in a zirconia ball milling jar, seal it and transfer it to a planetary ball mill for ball milling (the weight ratio of metal lithium to matrix material is 2:1), the ball-to-material ratio of ball milling is 20:1, the diameter of zirconium balls is 5.5mm, 3.0mm, 2.0mm, the ratio is 2:5:3, the ball milling speed is 800 rpm, and the ball milling time is 6 hours. Then add a total of 2g of ethylene carbonate and lithium hexafluorophosphate mixed solution to continue ball milling (the weight ratio of the raw material mixture to the composite solution is 1:0.67; the weight ratio of carbonate compounds to fluorine-containing compounds in the composite solution is 20:1), the ball milling speed is 400 rpm, and the ball milling time is 20 hours. After centrifugation, dry it in a vacuum drying oven at a drying temperature of 60°C for 8 hours to obtain stable metal lithium powder, recorded as L-2.
[0115] Figure 6 This is the Li 1s X-ray photoelectron high-resolution scanning spectrum of the stabilized lithium metal powder prepared in Example 2. As can be seen from the figure, obvious Li characteristic peaks appear in the material, indicating that the stabilized lithium metal powder sample still contains a large amount of active lithium.
[0116] Example 3
[0117] Under argon environment, weigh 2g of metal lithium ingot and 0.5g of silicon oxide and place them in a zirconium oxide ball milling jar, seal it and transfer it to a planetary ball mill for ball milling (the weight ratio of metal lithium to matrix material is 4:1), the ball-to-material ratio of ball milling is 20:1, the diameter of zirconium balls is 5.5mm, 3.0mm, 2.0mm, the ratio is 2:5:3, the ball milling speed is 500 rpm, and the ball milling time is 10 hours. Then add a total of 2g of ethylene carbonate, propylene carbonate and lithium hexafluorophosphate mixed solution to continue ball milling (the weight ratio of the raw material mixture to the composite solution is 1:0.8; the weight ratio of carbonate compounds to fluorine-containing compounds in the composite solution is 10:1, and the weight ratio of ethylene carbonate and propylene carbonate in the carbonate compounds is 1:1), the ball milling speed is 500 rpm, and the ball milling time is 5 hours. After centrifugation, dry it in a vacuum drying oven at a drying temperature of 100°C for 2 hours to obtain stable metal lithium powder, recorded as L-3.
[0118] Figures 7 to 9 The X-ray photoelectron high-resolution scanning spectra of C1s, O 1s and F1s of the stable metallic lithium powder prepared in Example 3 are respectively Figures 7 to 9 It can be seen that after the stable metallic lithium powder was passivated, characteristic peaks of lithium fluoride and lithium carbonate, the main components of the SEI film, appeared on the surface, indicating that a passivation layer containing lithium fluoride and lithium carbonate was formed on the surface of the metallic lithium powder.
[0119] Example 4
[0120] Under argon environment, weigh 2g of lithium metal ingot and 0.2g of silicon oxide and place them in a zirconium oxide ball mill (the weight ratio of lithium metal to matrix material is 10:1), seal and transfer to a planetary ball mill for ball milling, the ball-to-material ratio of the ball milling is 20:1, the diameter of the zirconium balls is 5.5mm, 3.0mm, 2.0mm, the ratio is 2:5:3, the ball milling speed is 500r / min, and the ball milling time is 12h. Then add a total of 2.2g of ethylene carbonate and phosphorus pentafluoride mixed solution to continue ball milling (the weight ratio of the raw material mixture to the composite solution is 1:1; the weight ratio of carbonate compounds to fluorine-containing compounds in the composite solution is 20:1), the ball milling speed is 350r / min, and the ball milling time is 10h. After centrifugation, dry in a vacuum drying oven at a drying temperature of 80℃ for 5h to obtain stable lithium metal powder, recorded as L-4.
[0121] The test data of component contents and structural parameters of the products obtained in the above examples and comparative examples are listed in the following Table 1.
[0122] Table 1
[0123]
[0124] In Table 1, the core content, buffer layer content and passivation layer content are calculated by raw material ratio.
[0125] Application Example 1
[0126] This application example is used to illustrate the application effect of the products obtained in the examples of the present application and the comparative examples in lithium batteries.
[0127] The preparation of the pre-lithiation negative electrode plate comprises the following steps:
[0128] (1) Silicon oxide powder (SiO y , y ranges from 0.5 to 1.2) as negative electrode active material, conductive agent, and binder are weighed in a ratio of 8:1:1, solvent water is added to adjust the slurry viscosity, and stirred for 3 hours to form a negative electrode slurry;
[0129] (2) coating the mixed negative electrode slurry on the copper foil current collector with a scraper mold, drying and rolling to obtain a negative electrode sheet;
[0130] (3) The stable lithium powder prepared in the example or the product obtained in the comparative example is dispersed in an N-methylpyrrolidone (NMP) solution containing 5 wt % polyvinylidene fluoride (PVDF) and stirred uniformly to prepare a lithium powder slurry with a lithium powder solid content of 5 wt %;
[0131] (4) coating the lithium powder slurry on the surface of the prepared negative electrode sheet in a low humidity environment to a coating thickness of 100 μm, vacuum drying, and rolling to obtain a pre-lithiated negative electrode sheet; wherein the weight ratio of the negative electrode active material to the lithium-containing material is 1:0.05;
[0132] (5) Punching the non-pre-lithiated negative electrode sheets and the pre-lithiated negative electrode sheets, assembling button-type half-cells respectively, leaving the sealed batteries to stand for 24 hours, and performing charge and discharge tests and cycle performance tests on the batteries using a Land battery performance test system.
[0133] The electrolyte was a 1M LiPF6 / EC:DMC (1:1, vol) mixed solution, and the separator was a Celgard 2300 polypropylene microporous membrane. The test results are listed in Table 2.
[0134] Table 2
[0135]
[0136] Fig.10 The electrochemical capacity-voltage test results of a lithium-ion battery assembled using the stable metallic lithium powder L-1 prepared in Example 1 as the pre-lithiation negative electrode material are as follows: the current density is 0.2C, the first charge specific capacity is 1003.06 mAh / g, the first discharge specific capacity is 1171.22 mAh / g, and the first coulombic efficiency is 85.6%.
[0137] According to the data in Table 2 above, compared with the battery test results of products D-1 to D-3 prepared by the comparative example, the battery test results of the stable lithium powders L-1 to L-4 prepared by Examples 1 to 4 of the present disclosure have higher first coulombic efficiency and 100 cycle capacity retention rate; and the slurry gas production can be avoided during the homogenization process.
[0138] The battery assembled using conventional silicon oxide that has not been pre-lithiated directly as the negative electrode material has an initial coulombic efficiency of approximately 69%, and a capacity retention rate of approximately 16% after 100 cycles. Compared with silicon oxide as the negative electrode material, the battery test results using the stable lithium powders L-1 to L-4 prepared in Examples 1 to 4 of the present disclosure have higher initial coulombic efficiency and 100 cycle capacity retention rate.
[0139] Furthermore, Example 1 and Example 4 adopt the preparation conditions in the preferred embodiment of the present disclosure during the preparation process. Therefore, compared with the stable lithium powders L-2 to L-3 prepared in Examples 2 to 3, the battery test results using L-1 and L-4 have higher first coulombic efficiency and 100 cycle capacity retention rate.
[0140] Application Examples 2-3
[0141] Referring to the method of Application Example 1, the difference from Application Example 1 is that:
[0142] The preparation conditions were changed during the preparation of the pre-lithiation negative electrode sheet, as shown in Table 3. The test results are listed in Table 3.
[0143] Table 3
[0144]
[0145]
[0146] By comparing Application Example 2 with Application Example 1, it can be seen that when the same lithium-containing material L-1 is used, the coating thickness of the lithium-containing material in Application Example 1 is in the range of 50 to 200 μm. Compared with Application Example 2, Application Example 1 can obtain higher first coulombic efficiency and cycle capacity retention rate.
[0147] According to Application Example 3, the lithium-containing material provided by the present disclosure can be used in combination with different types of negative electrode active materials and has a wide range of applications;
[0148] By comparing Application Example 4 with Application Example 1, it can be seen that when the same lithium-containing material L-1 is used, the weight ratio of the negative electrode active material to the lithium-containing material in Application Example 1 is in the range of 1:(0.01~0.1). Compared with Application Example 4, Application Example 1 can obtain higher first coulombic efficiency and cycle capacity retention rate.
[0149] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0150] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0151] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A lithium-containing material, characterized in that: The lithium-containing material comprises lithium-containing particles of a core-shell structure; the lithium-containing particles comprise a core, a buffer layer coated on the outer surface of the core, and a passivation layer coated on the outer surface of the buffer layer; the passivation layer forms an outer shell of the core-shell structure; wherein the core comprises a lithium active component and a matrix material, and the matrix material is selected from one or both of silicon and silicon monoxide; the buffer layer comprises a silicon-lithium alloy or lithium silicate; and the passivation layer comprises lithium fluoride and lithium carbonate.
2. The lithium-containing material according to claim 1, characterized in that Based on the total weight of the lithium-containing particles, the content of the core is 5 to 95% by weight, preferably 80 to 95% by weight; the content of the buffer layer is 5 to 35% by weight, preferably 5 to 10% by weight; the content of the passivation layer is 1 to 10% by weight, preferably 1 to 6% by weight; Optionally, the average particle size of the lithium-containing particles is 0.01 to 5 μm; and the thickness of the passivation layer of the lithium-containing particles is 1 to 500 nm.
3. A method for preparing a lithium-containing material, characterized in that: The following steps are involved: S1, mixing metallic lithium with a matrix material, and subjecting the mixture to ball milling to obtain a raw material mixture, wherein the matrix material is selected from one or both of silicon and silicon monoxide; S2, mixing the raw material mixture with the composite solution and performing a stabilization treatment; wherein the composite solution comprises a carbonate compound and a fluorine-containing compound; Steps S1 to S2 are respectively carried out under inert conditions.
4. The method according to claim 3, characterized in that In step S1, the weight ratio of the metallic lithium to the matrix material is (2-50):1, preferably (5-20):1; Optionally, the metallic lithium is selected from one or more of lithium ingots, lithium wires, lithium powders or lithium sheets; Preferably, in the matrix, silicon is in powder form, the average particle size of the silicon powder is 0.5 to 10 μm, and the BET specific surface area is 0.1 to 50 m 2 / g; the silicon oxide is a powder, the average particle size of the silicon oxide powder is 1 to 20 μm; the BET specific surface area is 0.5 to 100 m 2 / g.
5. The method according to claim 3, characterized in that: In step S1, the conditions of the ball milling treatment include: a rotation speed of 300 to 2000 r / min, preferably 500 to 1000 r / min; a time of 6 to 72 hours, preferably 10 to 48 hours; a ball-to-material ratio of (1 to 50):1, preferably (10 to 20):
1.
6. The method according to claim 3, characterized in that In step S2, the carbonate compound is selected from one or more of ethylene carbonate, propylene carbonate, diethyl carbonate and dimethyl carbonate; The fluorine-containing compound is selected from one or more of lithium hexafluorophosphate, phosphorus pentafluoride and hydrofluoric acid; Preferably, the weight ratio of the carbonate compound to the fluorine-containing compound in the composite solution is (1-50):1; preferably (5-20):1; Optionally, in step S2, the weight ratio of the raw material mixture to the composite solution is 1:(0.01-1), preferably 1:(0.5-1).
7. The method according to claim 3, characterized in that In step S2, the conditions for the stabilization treatment include: a ball milling speed of 200 to 1000 r / min, preferably 200 to 500 r / min; a time of 6 to 72 h, preferably 10 to 20 h; and a ball to material ratio of (1 to 50):1, preferably (10 to 20):
1.
8. The method according to claim 3, characterized in that After step S2, the method further comprises: Drying the product obtained by the stabilization treatment to obtain a lithium-containing material; Preferably, the drying treatment temperature is 60-100° C.; the drying time is 2-12 hours; preferably, the drying is performed in a vacuum drying oven.
9. The lithium-containing material prepared by the method according to any one of claims 3 to 8.
10. A pre-lithiation negative electrode plate, characterized in that: The pre-lithiation negative electrode plate comprises the lithium-containing material according to any one of claims 1 to 2 and claim 9.
11. The pre-lithiation negative electrode plate according to claim 10, characterized in that: The pre-lithiation negative electrode plate comprises a negative electrode active material and the lithium-containing material; Optionally, the negative electrode active material is selected from one or more of silicon oxide negative electrode materials, graphite negative electrode materials, silicon-carbon negative electrode materials and silicon negative electrode materials; Preferably, the weight ratio of the negative electrode active material to the lithium-containing material is 1:(0.01-0.5), preferably 1:(0.01-0.1); Optionally, the lithium-containing material is coated on the surface of the coating of the negative electrode active material in the form of a coating; preferably, the coating thickness of the lithium-containing material is 1 to 500 μm, preferably 50 to 200 μm.
12. A lithium-containing battery, characterized in that: It includes the pre-lithiation negative electrode plate as described in claim 10 or 11.
